Distal clavicle fracture following reverse shoulder arthroplasty: A case report - Yuki Yoshida; Atsushi Yoshida (Journal of Orthopaedic Reports)
Introduction: Reverse shoulder arthroplasty (RSA) has gained popularity to its positive clinical results, which enable patients to regain shoulder elevation by utilizing the deltoid muscle. However, several postoperative complications have been reported due to changes in anatomical position. Case report: Here we report a case of an 87-year-old female presenting with distal clavicle fracture following RSA. This fracture was assumed to be caused by excessive load on the deltoid muscle. Conclusion: Although acromial and scapular spine fractures are common postoperative complications of RSA due to excessive stress on the deltoid muscle, there is also the possibility of clavicle fractures. It should be aware the possibility of the fractures in areas where the deltoid muscle is loaded during RSA follow-up.